Morality and State in the Fichtean Political Philosophy - Arrese Igor, Hector Oscar (Araucaria, 2019)
The philosophy of history of 1804 and 1805 enables Fichte to place his natural right, developed previously at Jena, against a diachronic background. This means that Fichte does not reason merely synchronically from a timeless conception of society and state. From a synchronic viewpoint, Fichte cannot solve the problem of the control of political power because he has to draw on the assumption of a virtuous ephorate. This assumption is not consistent with the Fichtean ideal of a philosophy of right completely independent from moral considerations. Thus, the control of government is possible only if at least a group of citizens can go beyond the mere rational egoism. This new temporal conception of the state leads Fichte to think that the problems of consistency of his theory of Jena are unavoidable, given that a society integrated by egoist individuals cannot be sustained. However, his later philosophy of history enables Fichte to state the inexorable annihilation of this type of community and gives place to an ensuing epoch, when citizens are not self-interested anymore.